IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN DI SDN KETAWANGGEDE - Noviyanti, Shobihatul Fitroh; Alfaruqi, Nafis; Berliana, Ima; Fitriani, Wiji (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The Merdeka Curriculum is present as an effort to provide flexibility for educational units and educators in designing learning that meets the needs of students. SDN Ketawanggede implements the Merdeka Curriculum in its learning process. This research aims to describe the implementation of the Merdeka Curriculum in the learning process at SDN Ketawanggede.The research approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation.The research results show that SDN Ketawanggede has implemented the Merdeka Curriculum quite well through several points, namely teacher training and teaching methods.Teachers at SDN Ketawanggede also show enthusiasm in developing the learning process and adjusting, understanding the characteristics of the students so that the learning process at SDN Ketawanggede runs effectively. However, some obstacles are still found, such as limited facilities and infrastructure, as well as uneven understanding among teachers. This research concludes that although the implementation of the Merdeka Curriculum at SDN Ketawanggede is not yet fully optimal,it has shown a positive direction and has the potential to continue developing with ongoing support from various parties. This research concludes that although the implementation of the Merdeka Curriculum at SDN Ketawanggede is not yet fully optimal, it is already showing a positive direction and has the potential to continue developing with ongoing support from various parties.